Does equal education opportunity apply to undocumented children in Sabah? an assessment of the national education policy - Emmy, Liew; Saibeh, Badariah (Faculty of Administrative Science and Policy Studies, 2023)
Education is for all regardless of one’s race, colour, sex, language, religion, political or other opinion, national or social origin, property, birth or other status. Deprivation of education is the deprivation of basic human rights. The goal of this study is to examine the National Education Policy regarding the opportunity for education for undocumented children in Sabah. And secondly to understand the constraining factors in providing education to undocumented children. This study employs an exploratory qualitative, case study bound approach and uses semi-structured interviews in the data collection process. And uses non-probability purposive sampling in the sampling selection. Eleven respondents participate in the data collection process. The findings reveal that the undocumented children had no opportunity to access mainstream education, yet they had access to education through the ALCs which are operated by the NGOs. And laws, politics, and finances are the three main factors that constrain the provision of education to undocumented children. “Education for All” is the future hope of education in Malaysia. Political will and commitment are crucially important to fully rectify and uphold the international human rights treaties. Education is not a choice; it is a must. Therefore, the government must heighten its commitment to inclusive education and execute actions that may forward toward the achievement of “Education for All”.